MANAJEMEN PELAKSANAAN PEMBANGUNAN DESA DI DESA ENTAKAI JAWAI - Petrus Atong (Universitas Kapuas Sintang, 2024)
Research on the management of village development implementation was conducted to understand, examine and develop aspects of planning, organizing, mobilizing and supervising. The research method is descriptive, the research subjects consist of the Village Head and the Chairman of the Village Consultative Body. The research instruments consisted of interviews, documentation and observation. Data analysis is qualitative analysis. The results showed that the mobilization related to community participation was still low, where the community involved had not played an active role. The results of the research also found that other things that influence the management of village development implementation are related to community participation and funding sources in the implementation of development in the village.